Screen-printed electrode produced by printed-circuit board technology. Application to cancer biomarker detection by means of plastic antibody as sensing material - Moreira, Felismina T.C. (2017)
This research work presents, for the ﬁrst time, a screen-printed electrode (SPE) made on a PCB board with silver tracks (Ag) and a three electrode conﬁguration (AgxO-working, AgxO-counter and Ag/AgxO-reference electrodes), following the same approach as printed-circuit boards (PCBs). This low cost and disposable device was tested for screening a cancer biomarker in point-of-care. The selected biomarker was carcinogenic embryonic antigen (CEA) protein, routinely used to follow-up the progression of speciﬁc cancer diseases. The biosensor was constructed by assembling a plastic antibody on the Ag-working electrode area, acting as the biorecognition element of the device. The protein molecules that were entrapped on the polymer and positioned at the outer surface of the polypyrrole (PPy) ﬁlm were removed by protease action. The imprinting effect was tested by preparing non-imprinted (NPPy) material, including only PPy as biorecognition element. Infrared and Raman studies conﬁrmed the surface modiﬁcation of these electrodes. The ability of the sensing material to rebind CEA was measured by several electrochemi-cal techniques: cyclic voltammetry (CV), impedance spectroscopy (EIS) and square wave voltammetry (SWV). The linear response ranged from 0.05 to 1.25 pg/mL against logarithm concentration. Overall, producing screen-printed electrodes by means of conventional PCB technology showed promising features, mostly regarding cost and prompt availability. The plastic antibody-based biosensor also seems to be a promising tool for screening CEA in point-of-care, with low response time, low cost, good sensitivity and high stability.